Myeloid sarcoma involving the greater wing of the sphenoid bone and additional skeletal sites presenting with unilateral proptosis and fevers. (4th March 2019) - Wang, Jay C.; Jiménez Pérez, Juan C.; Friedmann, Alison M.; Louissaint, Abner; Freitag, Suzanne K.
ABSTRACT: We report a case of myeloid sarcoma with multifocal skeletal involvement, including the greater wing of the sphenoid bone. A 23-month-old boy presented with left-sided proptosis and fevers, and was found to have an infiltrative mass involving the left sphenoid bone on orbital imaging. Full body imaging further demonstrated multiple bony lesions in the pelvis, thoracic and lumbar vertebrae, bilateral femura, and left humerus, and biopsies of the humerus were consistent with myeloid sarcoma. The patient was started on a standard chemotherapy regimen and is responding well. Myeloid sarcoma presenting with proptosis due to sphenoid bone involvement with simultaneous multifocal skeletal involvement is very uncommon and highlights the importance of biopsy for establishing a definitive diagnosis.